Near‐infrared spectroscopy estimation of combined skeletal muscle oxidative capacity and O2 diffusion capacity in humans. (23rd August 2022) - Pilotto, Andrea M.; Adami, Alessandra; Mazzolari, Raffaele; Brocca, Lorenza; Crea, Emanuela; Zuccarelli, Lucrezia; Pellegrino, Maria A.; Bottinelli, Roberto; Grassi, Bruno; Rossiter, Harry B.; Porcelli, Simone
Abstract : Abstract: The final steps of the O2 cascade during exercise depend on the product of the microvascular‐to‐intramyocyte P O 2 P_O_2 difference and muscle O2 diffusing capacity ( D m O 2 Dm_O_2 ). Non‐invasive methods to determine D m O 2 Dm_O_2 in humans are currently unavailable. Muscle oxygen uptake (m V ̇ O 2 V_O_2 ) recovery rate constant ( k ), measured by near‐infrared spectroscopy (NIRS) using intermittent arterial occlusions, is associated with muscle oxidative capacity in vivo . We reasoned that k would be limited by D m O 2 Dm_O_2 when muscle oxygenation is low ( k LOW ), and hypothesized that: (i) k in well oxygenated muscle ( k HIGH ) is associated with maximal O2 flux in fibre bundles; and (ii) ∆k ( k HIGH – k LOW ) is associated with capillary density (CD). Vastus lateralis k was measured in 12 participants using NIRS after moderate exercise. The timing and duration of arterial occlusions were manipulated to maintain tissue saturation index within a 10% range either below (LOW) or above (HIGH) half‐maximal desaturation, assessed during sustained arterial occlusion. Maximal O2 flux in phosphorylating state was 37.7 ± 10.6 pmol s −1 mg −1 (∼5.8 ml min −1 100 g −1 ). CD ranged 348 to 586 mm –2 . k HIGH was greater than k LOW (3.15 ± 0.45 vs . 1.56 ± 0.79 min –1, P < 0.001). Maximal O2 flux was correlated with k HIGH ( r = 0.80, P = 0.002) but not k LOW ( r = –0.10, P = 0.755). Δ k ranged –0.26 to –2.55 min –1, and correlated with CD ( r = –0.68, P = 0.015). m V ̇ O 2 V_O_2 k reflects muscle oxidative capacity only in well oxygenated muscle. ∆k, the difference in k between well and poorly oxygenated muscle, was associated with CD, a mediator of D m O 2 Dm_O_2 . Assessment of muscle k and ∆k using NIRS provides a non‐invasive window on muscle oxidative and O2 diffusing capacity. Key points: We determined post‐exercise recovery kinetics of quadriceps muscle oxygen uptake (m V ̇ O 2 V_O_2 ) measured by near‐infrared spectroscopy (NIRS) in humans under conditions of both non‐limiting (HIGH) and limiting (LOW) O2 availability, for comparison with biopsy variables. The m V ̇ O 2 V_O_2 recovery rate constant in HIGH O2 availability was hypothesized to reflect muscle oxidative capacity ( k HIGH ) and the difference in k between HIGH and LOW O2 availability ( ∆k ) was hypothesized to reflect muscle O2 diffusing capacity. k HIGH was correlated with phosphorylating oxidative capacity of permeabilized muscle fibre bundles ( r = 0.80). ∆k was negatively correlated with capillary density ( r = −0.68) of biopsy samples. NIRS provides non‐invasive means of assessing both muscle oxidative and oxygen diffusing capacity in vivo . Abstract : Abstract figure legend A NIRS probe was positioned on vastus lateralis muscle and used to assess both muscle oxidative and oxygen diffusing capacity in vivo by intermittent arterial occlusions. Timing and duration of each occlusion were manipulated to maintain tissue saturation index within a 10 percentage range either below (LOW) or above (HIGH) half‐maximal desaturation. Recovery rate constant ( k ) of muscle oxygen consumption (m V ̇ O 2 V_O_2 ) obtained by NIRS was correlated with phosphorylating oxidative capacity of permeabilized muscle fibre bundles. Changes in recovery rate constant ( k ) were correlated with capillary density calculated from cross‐section of muscle samples obtained by immunofluorescence.